Applications of Normal S-Iterative Method to a Nonlinear Integral Equation - Faik Gürsoy (The Scientific World Journal)
It has been shown that a normal S-iterative method converges to the solution of a mixed type Volterra-Fredholm functional nonlinear integral equation. Furthermore, a data dependence result for the solution of this integral equation has been proven.